Positive Teacher Feedback on Learning Motivation and Mental Health of Early Childhood - Firmansyah, Aidil Ikal; Putra, Bramana Nanditya; Komsi, Dwi Noviana (Journal of Childhood Development, 2025)
This study aims to describe the role of positive teacher feedback in improving learning motivation and mental health of early childhood children at Silampari Islamic School Kindergarten, Lubuk Linggau. Using a qualitative approach with observation, interviews, and documentation methods, this study explores how forms of positive reinforcement are provided and how children respond to these practices. The results show that positive feedback, such as verbal praise, affective expressions, and nonverbal reinforcement, can create a supportive, safe classroom atmosphere and boost children's self-confidence. Teachers, children, and the principal confirmed that an appreciative classroom climate contributes to increased learning motivation, a sense of comfort, and reduced anxiety in children during the learning process. This study confirms that a culture of appreciation is an important strategy in early childhood education to support both academic development and emotional well-being.